Adapting the Resilience Framework for Family Caregivers of Hospice Patients With Dementia. Issue 6 (September 2019) - Han, Soojeong; Chi, Nai-Ching; Han, Claire; Oliver, Debra Parker; Washington, Karla; Demiris, George
Family caregivers face ongoing, formidable stress and burden. Caregivers need sustainable support to maintain resilience. We aim to identify challenges, possible solutions that are resources for resilience, and expected consequences from the perspective of 39 family caregivers of hospice patients with dementia. The resilience framework was used to guide the coding and synthesis of the qualitative data. Identified challenges included difficulties in communication, providing care and decision-making, lack of knowledge, emotional challenges, concern about care facility selection, death with dignity, and lack of public awareness. Resilience resources for caregiving challenges were identified at the individual, community, and societal levels. Anticipated benefits of using these resources included the ability to provide better care and have a better quality of life for both patients and caregivers. The findings of this study can guide the design and implementation of supportive interventions designed for family caregivers of hospice patients with dementia to bolster available resilience resources.